Análisis del modelo de evaluación del desfinanciamiento de la educación superior estatal en la Universidad del Quindío (2013)
Higher education in Colombia has undergone major changes since the creation of the Law 30 of 1992, which organizes public service of universities in Colombia and make the State University System, the law, has had a major failure in the system financial public universities in the country, due to the severe limitations that this has brought over the years. The growth of public HEIs by increasing student academic programs and has created conditions unsuitable for operation, which is evidenced by deficiencies in physical infrastructure, availability of spaces such as libraries, technological and audiovisual resources, and few plant teachers, among others.